Dispersed repetitive DNA sequence of Mucor racemosus. - Dewar, R (1985)
A dispersed repetitive DNA sequence has been identified within the genome of the fungus Mucor racemosus. Recombinant phage clones, as well as a plasmid harboring the sequence, have been isolated. Examination of cloned fragments comprising part of the repetitive sequence has led to a partial characterization of the element. The sequence has been detected in other Mucor species, and although the apparent number and chromosomal position of the repetitive sequence vary from strain to strain, it is clear that at least portions of the element have been conserved.